2015
DOI: 10.18632/oncotarget.4213
|View full text |Cite
|
Sign up to set email alerts
|

Mastocytosis: a mutated KIT receptor induced myeloproliferative disorder

Abstract: Although more than 90% systemic mastocytosis (SM) patients express gain of function mutations in the KIT receptor, recent next generation sequencing has revealed the presence of several additional genetic and epigenetic mutations in a subset of these patients, which confer poor prognosis and inferior overall survival. A clear understanding of how genetic and epigenetic mutations cooperate in regulating the tremendous heterogeneity observed in these patients will be essential for designing effective treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 87 publications
0
64
0
5
Order By: Relevance
“…Mastocytose tenkes å ha sitt opphav fra muterte hematopoetiske stamceller (12). Studier har vist at > 90 % av pasientene har en aktiverende mutasjon i genet KIT, der over 80 % av disse vil ha en bestemt punktmutasjon i ekson 17, KITD816 V (13,14). KIT er en transmembran tyrosinkinasereseptor for stamcellefaktor CD117 (6,13).…”
Section: Figur 3 Diagnostisk Algoritme For Systemisk Mastocytose Diaunclassified
See 1 more Smart Citation
“…Mastocytose tenkes å ha sitt opphav fra muterte hematopoetiske stamceller (12). Studier har vist at > 90 % av pasientene har en aktiverende mutasjon i genet KIT, der over 80 % av disse vil ha en bestemt punktmutasjon i ekson 17, KITD816 V (13,14). KIT er en transmembran tyrosinkinasereseptor for stamcellefaktor CD117 (6,13).…”
Section: Figur 3 Diagnostisk Algoritme For Systemisk Mastocytose Diaunclassified
“…To uker etter at pasienten kom hjem fra sykehuset, viste blodprøver tatt hos fastlegen nytilkommet anemi med hemoglobin 11,5 g/dl (13,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Automatisk differensialtelling tatt ved fastlegekontoret anga «blastalarm», og det ble utført supplerende blodutstryk som ble vurdert av hematolog ved lokalsykehuset.…”
unclassified
“…Гепатолиенальная Т-клеточная лимфома 7q i (7) [6,115,116] Системный мастоцитоз (+/-поражение кожи) Системный мастоцитоз, сочетающийся с гематологическими нарушениями (+/-поражение кожи) Тучноклеточный лейкоз/саркома даст возможность разработать новые молекулы для доклинических и клинических исследований и/или перепрофилировать уже известные препараты, что может привести к оптимизации терапевтической тактики и улучшению показателей выживаемости пациентов.…”
Section: Cltc-alkunclassified
“…In the light of increased, atypical mast cells on bone marrow evaluation, elevated tryptase (158 μg/l), and clinical symptoms including flushing, tachycardia, and hypotension, evaluation for systemic mastocytosis was undertaken. Molecular study for the KIT D816V mutation was negative, but next‐generation sequencing identified a KIT D816H in the peripheral blood, fulfilling diagnostic criteria for systemic mastocytosis with associated hematological nonmast cell disease, specifically SM‐CMML . Next‐generation sequencing was also performed on the GCT and identified the identical KIT mutation in both the teratoma and the dysgerminoma components; the yolk sac tumor was not evaluated.…”
Section: Case Reportmentioning
confidence: 99%